(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
A cryptocurrency is a digital currency that utilises an encryption algorithm to create an alternative form of payment. Cryptocurrencies may be utilised as money and a virtual accounting system due to encryption technology. To utilise cryptocurrencies, you will need a wallet. The current exchange rate situation is bearish, or what they call falling prices on coins. With the proliferation of cryptocurrencies in the Bestlink College of the Philippines, its problems are still increasing. For example, digital currency’s highest risk is price volatility. Although cryptocurrency transactions eliminate cyber threats like stolen credit card numbers, the currency still is not 100% safe from cybersecurity threats. This study used a descriptive research method of design. The study’s respondents were fifteen (15) crypto players of Bestlink College of the Philippines. This study utilised a purposive sampling technique. Data were tallied and analysed using frequency, percentage, and weighted mean. The findings of the study revealed that the majority of the cryptocurrency exchange rates in the market towards customers’ expectations in the age group of 21-25 years old, the majority of the gender is more males, the majority of respondents are in lower-income, majority of them also use their payment transaction is Gcash, as the majority of the NFT played is Axie Infinity, while only a few are in Plants vs Undead, MiR4. Lastly, most crypto players have token values ​​such as USDT, BNB, and BTC. The majority of the level of demand increases when there are fast transactions and low prices. All variables on the cryptocurrency exchange rate meet the level of customers’ expectation were Exceed Expectation. Based on the information gathered, this research could help crypto players improve their perception by considering the recommendations. This includes further expansion and growth of the cryptocurrency to make it more accessible, convenient, and secure for its customers and users, allowing players to earn money too. Cryptocurrency must continue to provide good customer feedback and meet the customers’ expectations because this is one of the reasons for cryptocurrency to grow and spread even more globally.